2019
DOI: 10.1039/c9gc01116a
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-catalyzed intelligent reductive transformation of the aldehyde group using hydrogen

Abstract: A highly efficient and catalytic valorization of lignin-derived aldehydes to produce value-added chemicals has been developed using a Ni-based catalyst under H2 atmosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…The elemental distribution of elements in Figure 1C was known, and we found that carbon, nitrogen, oxygen and nickel element were distributed homogeneously throughout the Ni-BTC structure. Our results with regard to the structure of synthesized Ni-BTC MOF materials ( Figure 1D) appear to be in agreement with those reported elsewhere [35]. These results were also in agreement with our X-ray spectroscopy (XPS) spectrum ( Figure S1).…”
Section: Synthesis and Characterization Of Ni-btcsupporting
confidence: 93%
See 1 more Smart Citation
“…The elemental distribution of elements in Figure 1C was known, and we found that carbon, nitrogen, oxygen and nickel element were distributed homogeneously throughout the Ni-BTC structure. Our results with regard to the structure of synthesized Ni-BTC MOF materials ( Figure 1D) appear to be in agreement with those reported elsewhere [35]. These results were also in agreement with our X-ray spectroscopy (XPS) spectrum ( Figure S1).…”
Section: Synthesis and Characterization Of Ni-btcsupporting
confidence: 93%
“…The chemical structure of Ni-BTC nanorods had been characterized previously which provided us with knowledge about the linker's integration and the oriented growth of the Ni-BTC nanorods and its cubic geometry [35]. As shown in Figure S2, Ni-BTC nanorods kept stable at temperatures below 100 • C and showed weight loss (26.1 wt %) between 100 • C and 300 • C, the reason might be the vaporization of water and solvent.…”
Section: Synthesis and Characterization Of Ni-btcmentioning
confidence: 99%
“…Tong, Liao et al. developed a Ni‐based material, designed as Ni‐MFC, for the selective production of 2‐methoxy‐4‐(methoxymethyl)phenol from vanillin and MeOH (Scheme 9N) [95] . In this work, optimum Ni catalyst was fabricated from N 2 ‐pyrolysis of a 2D Ni‐MOF ([Ni(tia)(H 2 O) 2 ] ∞ ) [tia 2− =5‐( 1H ‐1,2,3‐triazol‐1‐yl) isophthalate] at 500 °C.…”
Section: Reductive Etherification Of Alcohols or Surrogates With Aldehydes/ketonesmentioning
confidence: 99%
“…Unlike traditional supported catalysts, the active sites of MOF-based catalysts can originate from metal linkers or immobilized metal NPs, and sometimes can also originate from functional groups present on organic ligands. [143] The gallate-based MOFs, namely Mgallate (M=Ni, Mn, Co), are selected as a feedstock for the synthesis of metal based catalysts due to their simple methods and ready availability. [144] Zhu et al [139a] synthesized gallatebased MOFs, namely, Ni x Co 1À x /C catalysts can afford monophenols in a yield of 55.2 % and guaiacol with a selectivity as high as 70.30 %.…”
Section: Metal-organic Framework Materialsmentioning
confidence: 99%
“…Moreover, inorganic nodes of MOFs that have recently been functionalized by incorporated into heteroatoms (N, S, B, Si) can active metal sites and other functional groups, endowing these functional MOF catalysts (e. g., NiÀ MFC-500, Ni/NÀ C-450, Ni@ZIF-8, Co/C@N) with good hydrogenolysis activity towards CÀ O bonds in lignin. [41,143,147] MIL-101-Cr as a catalyst support show high crystallinity, stability in water, thermal stability and Lewis acidity. Palladium NPs encapsulated in MIL-101-Cr was synthesized for the selective breaking of lignin βÀ OÀ 4 linkages through CTH reaction.…”
Section: Metal-organic Framework Materialsmentioning
confidence: 99%